1996
DOI: 10.1080/00071669608417847
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ubiquinone (coenzyme Q9) on ascites in broiler chickens

Abstract: 1. The effect of ubiquinone (CoQ(9)) on ascites in broiler chickens was investigated. 2. The commercial broilers were divided into 2 groups of 100 birds each; CoQ(9) treated group and non-treated group. 3. The chickens were grown in a positive-pressured house with double high efficiency particulate air filtered intakes and exhaust, and thus were strictly isolated from infectious agents. 4. The chickens (15 to 21 d old) were exposed to cold stress in order to induce ascites. 5. The number of birds with ascites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
3
13
0
Order By: Relevance
“…In addition, its reduced form -CoQH 2 (ubiquinol) -can act as an important antioxidant, lowering the accumulation of free radicals, particularly of ROS, thereby reducing peroxidative damage to the body (Forsmark-Andrée et al, 1997). Nakamura (1996) fed diets supplemented with coenzyme Q 9 , an analogue of CoQ 10 , at 40 mg/ kg to broiler chicks and showed that dietary coenzyme Q 9 supplementation reduced the incidence of ascites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, its reduced form -CoQH 2 (ubiquinol) -can act as an important antioxidant, lowering the accumulation of free radicals, particularly of ROS, thereby reducing peroxidative damage to the body (Forsmark-Andrée et al, 1997). Nakamura (1996) fed diets supplemented with coenzyme Q 9 , an analogue of CoQ 10 , at 40 mg/ kg to broiler chicks and showed that dietary coenzyme Q 9 supplementation reduced the incidence of ascites.…”
Section: Introductionmentioning
confidence: 99%
“…But at 40 mg kgG 1 of diet supplementation the incidence of leg problem was high (Geng et al, 2004a). This reduction in ascites mortality (around 40%) was observed when broiler fed CoQ9 (Nakamura et al, 1996). These studies imply that CoQ either 9 or 10 isoprene units are able to reduce the broiler's mortality due to ascites.…”
Section: Coenzyme Q10 On Ascites Heart Index (Ahi) and Ascites Mortalitymentioning
confidence: 58%
“…The CoQ10 showed hematopoietic activity by prolonged hematopoietic response in the peripheral blood and bone marrow in children having marasmus or kwashiorkor (Majaj and Folkers, 1968). However, in healthy broiler CoQ10 supplementation did not affected the PCV percent (Geng et al, 2004a, b;Asadi et al, 2013;Gopi, 2013) and also with CoQ9 supplementation (Nakamura et al, 1996). The Erythrocyte Osmotic Fragility (EOF %), reflects the degree of erythrocyte membrane extensibility and erythrocytes cell geometry (Gharaibeh et al, 1993).…”
Section: Coenzyme Q10 On Blood Picturementioning
confidence: 99%
See 2 more Smart Citations